Teach yourself VISUALLY MacBook - Miser, Brad. (Indianapolis : Wiley, 2008)
Presents instructions for more than 160 MacBook tasks, including usi ng the dock and dashboard, setting up a .Mac account, video chatting wi th iChat, and creating albums in iPhoto.
Chapter 1: Explore the MacBook.Tour MacBook.Start Up and Log In.Expl ore the Mac OS X Desktop.Point and Click, Double-click, or Right-click. Understand Disks, Volumes, Discs, Folders, and Files.Sleep, Log Out, Re start, or Shut Down.Chapter 2: Look Through Mac OS X Finder Windows.Und erstand Finder, Application, and Document Windows.Open, View, and Scrol l in Windows.Minimize, Resize, Move, or Close Windows.View Finder Windo ws in Icon View.View Finder Windows in List View.View Finder Windows in Column View.View Finder Windows in Cover Flow View.Configure the Sideb ar.Use the Action Pop-up Menu and Quick Look.Configure the Finder Windo w Toolbar.Chapter 3: Manage the Desktop with the Dock, Expose, Spaces, and the Dashboard.Explore the Dock, Expose, Spaces, and the Dashboard.U se and Configure the Dock.Manage Open Windows with Expose.Create and Us e Desktop Spaces.Use and Configure the Dashboard.Chapter 4: Work on the Mac Desktop.Go Places.Return to Where You Have Been Before.Open Files and Folders.Move or Copy Folders and Files.Create Folders.Create Smart Folders.Rename Files and Folders.Compress Files and Folders.Delete File s and Folders.Eject Disks and Discs.Find Files, Folders, and Other Info rmation.Get Information about Files and Folders.Burn a CD or DVD.Chapte r 5: Work with Mac Applications.Understand Applications.Install Applica tions.Launch and Control Applications.Remove Applications.Save Document s.Chapter 6: Personalize Your MacBook.Set Finder Preferences.Explore th e System Preferences Application.Change the Desktop's Appearance.Set a Desktop Picture.Choose a Screen Saver.Save Energy.Configure MacBook's S creen.Configure the Keyboard and Trackpad.Control MacBook's Sound.Creat e and Configure User Accounts.Set Login Options.Set and Configure MacBo ok's Clock.Protect Users with Parental Controls.Chapter 7: Connect to a Network and the Internet.Understand Networking Concepts.Obtain an Inte rnet Account.Set Up a Local Network.Protect MacBook from Internet Attac ks.Connect to the Internet with Ethernet.Connect to the Internet with A irPort.Share Files on a Local Network.Troubleshoot an Internet Connecti on.Chapter 8: Surf the Web.Explore Safari.Move to Web Sites.Search the Web.Download Files.Browse the Web with Tabs.Set and Organize Bookmarks. Open Several Web Pages at the Same Time.Watch Movies on the Web.Use Aut oFill to Quickly Complete Web Forms.Create Your Own Web Widget .Save or E-mail Web Pages.Set Safari Preferences.Chapter 9: E-mail.Explore Mail .Set Up E-mail Accounts.Read and Reply to E-mail.Send E-mail.Work with Files Attached to E-mail.Attach Files to E-mail.Organize E-mail.Search E-mail.Avoid Spam.Create and Use E-mail Signatures.Create E-mail Rules. Set Mail Preferences.Chapter 10: Use .Mac.Explore .Mac.Obtain and Confi gure a .Mac Account.Use an iDisk.Use .Mac Webmail.Publish a .Mac Web Si te.Synchronize Bookmarks, Contacts, and Calendars among Multiple Macs.C hapter 11: Listen to Music and Watch Video with iTunes.Explore iTunes.U nderstand the iTunes Library.Browse or Search for iTunes Content.Browse the Library with Cover Flow View.Browse the Library with Group View.Li sten to Audio Content.Watch Video Content.Add Audio CDs to the iTunes L ibrary.Explore the iTunes Store.Obtain and Log Into an iTunes Store Acc ount.Buy Music, TV, Movies, and More from the iTunes Store.Subscribe to Podcasts.Create a Standard Playlist.Create a Smart Playlist.Burn a CD or DVD.Chapter 12: Create Photo Books and Other Projects with iPhoto.Ex plore iPhoto.Import Photos from a Digital Camera.244Browse and Search t he iPhoto Library.246Label Photos.Edit Photos.Organize a Photo Book.s P hotos in an Album.Create a Photo Book.Lay Out a Photo Book.Edit a Photo Book.Configure a Photo Book.s Settings.Print a Photo Book.Chapter 13: Chat.Explore iChat.Configure an iChat Account.Chat with Text.Chat with Audio.Chat with Video.Share MacBook's Desktop.Chapter 14: Manage Contac ts.The Address Book Window.Understand Address Book.Add a Contact Manual ly.Work with vCards.Find Contact Information.Create an Address Group.Us e Address Cards and Groups.Change or Delete Address Cards or Groups.Cha pter 15: Manage Calendars.Explore iCal.Add a Calendar.Add an Event to a Calendar.Add a To Do Item to a Calendar.Publish Calendars.Subscribe to Calendars.Configure iCal Preferences.Chapter 16: Print on Paper or Ele ctronically.Understand Printers.Install and Configure a USB Printer.Ins tall and Configure a Networked Printer.Share a Printer.Connect to a Pri nter Wirelessly.Print to PDF.Chapter 17: Travel with a MacBook.Connect to the Internet while Traveling.Manage MacBook.s Power.Protect MacBook' s Data with FileVault.Protect MacBook with System Security.Protect MacB ook with Its Firewall.Synchronize Files with Other Computers.Chapter 18 : Connect a MacBook to Other Devices.Expand Storage Space with an Exter nal Hard Drive.Connect and Use an External Display.Connect and Use a Bl uetooth Mouse.Connect and Use External Speakers.Synchronize a MacBook w ith an iPhone.Chapter 19: Maintain and Troubleshoot MacBook.Keep MacBoo k's Apple Software Current.Maintain and Update Third-Party Applications .Profile MacBook.Monitor MacBook's Activity.Maintain MacBook's Hard Dri ve.Use Time Machine to Back Up MacBook.Restore Files with Time Machine. Troubleshoot and Solve MacBook Problems.Capture a Screenshot.Get Help w ith MacBook Problems.
Includes index.
Keywords: Macintosh (Computer) -- Handbooks, manuals, etc